Seasonal food availability calendar: Community user guide - Nabuuma, Deborah; Ekesa, Beatrice (2024)
Seasonal food availability calendars provide information that can be used to empower local communities to improve their access and utilisation of diverse foods all year round using locally available foods. This brief Community user guide was developed to assist nutrition and agricultural champions as they use seasonal food availability calendars in their communities.